Devising and Validating the Adolescent Attachment Styles Questionnaire (AASQ) - Pajaohande, Ali; Farzad, Valiolah; Kadivar, Parvin (International Journal of Education and Cognitive Sciences, 2022)
Introduction: One of the most influential and current theories that opened new windows towards the horizon of theorizing and psychotherapy is attachment theory that was developed out of works by Bowlby and Ainsworth. Of course it is worth noting that nearly none of the measures in this area specifically devised for the adolescence. So the purpose of this study is to Devise and Validate the Adolescent Attachment Styles Questionnaire (AASQ).Materials and methods:  Present study, was conducted on 380 high school students from Mashhad by employing Exploratory Factor Analysis (EFA) utilizing principal components method. Results: Finding reveals that three factors were extracted which were similar to categories described by Ainsworth; then, the validity of instrument was indicated through confirmatory factor analysis (CFA). Finally, the AASQ which includes 23 items and high internal consistency coefficients is presented.Conclusion: AASQ can be applied for adolescence but due to some limitations of the AASQ and also the significant difference between boys and girls in this questionnaire, it is recommended that the questionnaire will be separately normalized for each gender.